Coloproctology - Herold, Alexander; Lehur, Paul-Antoine; Matzel, Klaus E.; O'Connell, P. Ronan (European Manual of Medicine,, 2008)
EMM: Coloproctology presents the state-of-the-art in coloproctology. The topics covered include anatomy, physiology, anal disorders, dermatology, functional disorders, inflammatory bowel disease, benign and malignant tumours, endoscopy, emergencies and pain syndromes. All chapters give a comprehensive overview of etiology, incidence, epidemiology, diagnostics, medical and surgical treatment, complications and individual special considerations. This work presents surgical trainees with a comprehensive and condensed guide to the core knowledge required for the European Board of Surgery Qualification (EBSQ) examination. The manual will also be of assistance to practicing coloproctologists across Europe and beyond who have interest in continued professional development. Written by an international team of experts who have each made noteworthy contributions in their field, the coverage of most aspects of coloproctology in an easy to follow format also makes this manual valuable to other specialists.